Water Resources Conference: Watershed Planning in Maine - Houtman, Nick (Maine Policy Review, 1994)
Watershed planning in Maine suffers from several problems that were identified during a water resources conference held at the University of Maine in April 1994. A brief summary of key conference findings is reported here.